Swimming exercise transiently decrease lung diffusing capacity in elite swimmers - García, I.; Drobnic, F.; Pons, V.; Viscor, G. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Swimmers have larger lungs and a higher diffusion capacity than other athletes, but it remains unknown whether swimming exercise changes lung diffusing properties. This study aimed to evaluate modifications in pulmonary alveolar-capillary diffusion after swimming exercise. METHODS: The participants were 21 elite level swimmers, including 7 females and 14 males, with a training volume of 45-70 kilometers of swimming per week. The single-breath method was used to measure the lung diffusing capacity for carbon monoxide (DLCO) and the transfer coefficient of the lungs for carbon monoxide (KCO) before and after 10 training sessions over 4 weeks along 207 pre- to postevaluations. RESULTS: Swimming training consistently decreased lung diffusion capacity during the follow-up period, both DLCO (44.4±8.1 to 43.3±8.9 mL/min/mmHg, P=0.047, Eta²p=0.55) and KCO (5.92±0.79 to 5.70±0.81 mL/min/mmHg/L, P=0.003, Eta²p=0.75). CONCLUSIONS: Elite swimmers experience a subclinical impairment in lung diffusing capacity after swimming exercise, but the stress caused by swimming on the lungs and the acute reduction in DLCO does not lead to physiological dysfunction.